Governors and Governing Institutions: A Comparative Study of State-Business Relations in Russia's Regions - Gharafutdinova, Gulnaz; Kisunko, Gregory (World Bank Group, Washington, DC, 2014)
The paper uses the latest 2011 round of the Business Environment and Enterprise Performance Survey for the Russian Federation, which for the first time was designed to be representative of Russian regions. The paper takes a closer look at regional-level factors influencing the business environment in Russia and, more specifically, conditions that favor the emergence of symbiotic relations between regional authorities and regional businesses. Considering the argued significance of informal rules, norms, and agreements for the regional-level business environment in Russia, the paper uses proxy variables such as tenure and origin of regional governors to identify how these rules are being institutionalized. The findings reveal that, at least in case of Russia, juxtaposing the state and business actors as separate and opposed to each other may overstate the distinction between these two groups of actors and understate the fact that many localities in Russia have witnessed the emergence of mutually beneficial state-business arrangements. Defining whether these arrangements are beneficial or harmful to regional development is beyond the scope of this exploratory paper.